Contribution Of Game Traditional To Relationship Social Relations Of Children Schools - Criezta Korlefura; Theophanny Paula Theresia Rampisela; Jeanete Ophilia Papilaya; R F Tuasikal (EDU SCIENCES JOURNAL, 2020)
Playing gives children the possibility of active participation and enables development, achieving confidence and better in relations between groups. Through games children can learn social skills and obtain certain rules in games that are temporarily played. Departing this, the purpose of this study was to see how much the contribution of traditional games to the quality of children's social relations at school. This ability is included in the socioemotional aspect. After knowing, the goal in the future also wants to make a model that contains the procedures for applying traditional play methods in the curriculum / school subjects to be able to help children develop optimally the socioemotional aspects. The research method used is the qualitative and quantitative approaches. Quantitative approaches are used primarily about the presentation of children's social behaviors in school; while the qualitative approach is used more intensively in the analysis of the quality of children's social relations, along with the profile and results of the treatment given. The procedures used in this study are research and development procedures. Research and development procedures are used based on the reason that this study is intended to get an initial picture of the quality of children's social relations and it is hoped that in the next research it can produce a product that is the application of traditional games in subjects that aim to improve children's social relations skills. There are some findings obtained first, the results that children who are involved in some traditional games that are performed look more able to do teamwork or good communication with friends. They are indirectly trained in good communication skills and strategies. Secondly, they also after doing a game together, they tend to invite their friends in class to do the same thing. Third, children who are involved in traditional games have a good increase in gross motor activities